Det Allra bästa premiepensionssystemet? – varför skadan orsakad inom det svenska premiepensionssystemet är att betrakta som state-corporate crimes - Evelina Jansson (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract During the last few years, it has been revealed that Allra, a company that operated within the Swedish premium pension system, has acted reprehensively. In 2017 it was reported that Allra´s funds were expensive with mediocre growth and that owners at Allra benefitted at the expense of premium pension holders. Furthermore, Allra maintained subsidiaries in low tax jurisdictions that reduced tax revenues of the Swedish state and contributed to cash outflow. While this article was being written, Allra was also accused of potentially illegal transactions with a company named Oak Capital and suspected of overseeing illegal transactions between its subsidiaries in Luxembourg and Dubai. It is assumed that these transactions were made to enrich the shareholders of Allra. The current study, however, is disinterested in establishing Allra’s criminal guilt. Instead, it focuses on the role that private actors and state authorities have played in Allra’s harmful actions and potentially illegal transactions that have harmed premium pension holders and Swedish citizens. Using a theoretical framework proposed by Diane Vaughan (1983), the study explores issues of social structure and social relations. This is done in order to determine whether the social structure has played an important role in facilitating harm and whether states can be considered involved in this and, if so if it can be considered a case of state-corporate crime. The study concludes that states have been important for upholding and promoting the social structure and that the case can, therefore, be considered an example of statecorporate crime. However, since shareholders in leading positions in Allra have benefitted by using Allra as a tool, it is suggested that the concept of statecorporate crimes be broadened to include individuals and their self-interests.